Universo encantado do cuidado na autopoiese docente: uma viagem epistemológica transdisciplinar - Sampaio, Ana Tania Lopes (2010)
The health transition experienced in Brazilian health care model requires a metamorphosis in human and society, placing new demands on health and education. The Faculty of Science, Culture and Extension of Rio Grande do Norte (Facex), aware of their responsibilities to the Health System, which brings the principle of comprehensiveness as its structural axis, dared to implement a course of nursing in complex thinking and Experiential Pedagogy Humanescente with curriculum inter / transdisciplinary. For deployment of proprosta was not enough to reform thinking of educators, there was a need corporalizar new teaching practices that are aimed at the integral formation of human beings. In this context, emerged the workshop on Human Education autopoietic, self-forming area of the educator, where he developed an Action Research Existential (PA-E) which enabled experience, describe and analyze how the human autopoietic educators could contribute to the practice educational humanescente transdisciplinary curriculum project. Were worked out in meetings, knowledge necessary to practice the transdisciplinary 1st Meeting - learn to create; 2nd Meeting - learn to recognize the laws of nature with emphasis on complexity theory, 3rd Meeting - learn to organize, 4th meeting - namely autoestruturar themselves; 5th Meeting - know how to choose, 6th Meeting - knowing innovate 7th Meeting - namely exchange. Next an autobiographical perspective, we chose the metaphorical possibility to narrate the ways and strategies covered by the author and apprentice in the company of the Little Prince de Saint-Exupery, in search of a sensible pedagogical practice complex, which promotes re-enchant transdisicplinar education. The route involved five methodological connections: a literature review which relate to training for care in undergraduate nursing: the study of learning processes that drive the formation humanopoiética, emphasizing the relationship that involves the complexity and embodiment in the educational process transdisciplinary, highlighting the analysis of what is to learn from the findings of biosciences and recent cognitive theories of Maturana and Varela, the description of the interdisciplinary curriculum of the nursing course of Facex and Training Workshop, Human autopoietic, with emphasis on Experiential Education Humanescente; the report of seven meetings of the Workshops (cocoon), recording the experiences and listening to educators (luminescent butterflies), the final reflections with learning opportunized. Experientiality lived through, the expressions and words, educators say the influence of workshops for their teaching practices, highlighting it as a space for selforganizing, creating, learning and enchantment, and can identify the workshop as a place of transformation necessary for deployment an interdisciplinary curriculum. The knowledge emerging from the study indicate the need for permanent spaces of self, in which the educator learns from its body, between cognitive processes and vital, and in the experiences of their formative process the opportunity to act on the dimensions of knowing and being